2002
DOI: 10.1007/s00330-002-1351-0
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the normal appendix in children

Abstract: Our objective was to assess the ability of MR imaging in the detection of the normal appendix, and to describe the MR appearance of the normal appendix. There were 15 healthy volunteers (11 girls, 4 boys; mean age 12.3 years) who underwent MR imaging on a 1.0-T unit. The imaging protocol included axial and coronal T2-weighted ultra turbo spin-echo (UTSE)-weighted images, axial T1-weighted turbo spin-echo (TSE) and coronal short tau inversion recovery (STIR)/TSE sequences. Confidence regarding the detection was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 24 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…MRI has been reported to obtain good results for excluding or detecting appendicitis [13][14][15][16][17]19]. Our prospective study in a large group of patients confirms that MRI yields excellent diagnostic results and markedly decreases the negative appendectomy rate, without an increase in perforation rate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…MRI has been reported to obtain good results for excluding or detecting appendicitis [13][14][15][16][17]19]. Our prospective study in a large group of patients confirms that MRI yields excellent diagnostic results and markedly decreases the negative appendectomy rate, without an increase in perforation rate.…”
Section: Discussionsupporting
confidence: 90%
“…Technological developments have made ultrafast sequences possible, resulting in shorter examination times and fewer motion artifacts. Detection of appendicitis with MRI has been published in a small group of pregnant and non-pregnant patients [13][14][15][16][17][18][19]. This is, to our knowledge, the first prospective blinded clinical study, in more than 100 patients, to evaluate MRI in patients clinically suspected of having appendicitis.…”
Section: Introductionmentioning
confidence: 94%
“…Detection of the normal appendix was possible in 18 of 20 patients (90%) and was consistently demonstrated to the coronal section, both on the T1WI and T2WI images. Hormann et al (30) reported that the normal appendix was described by T2WI and T1WI, in 86% and 73% of children, respectively. On T2WI, the normal appendix had a hyperintense center and a hypointense wall, and was mostly hypointense on T1WI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sensitivity and specificity of CT for appendicitis in children are quite high (greater than 90% for both [5]), CT also has disadvantages, including use of ionizing radiation and associated risks (8,9), need for intravenous contrast material, and relatively limited soft-tissue contrast resolution. Several recent studies in children have shown that magnetic resonance (MR) imaging may be a viable alternative to CT for the evaluation of appendicitis when US is insufficient (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). MR imaging offers very high soft-tissue contrast resolution (which is particularly helpful in young children with a paucity of intra-abdominal fat), is nonionizing, and can be performed without intravenous or oral contrast material.…”
Section: Subject Identificationmentioning
confidence: 99%